HIV & AIDS Education and Prevention Efforts in Sukamulya Village - Daipah, Almatu; Budi Munawar Hutomi; Acip; Tiara Salsabilla; Yana Mulyana (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
HIV and AIDS is still a serious problem in public health, especially in rural areas with limited access to information and education. Sukamulya village faced this challenge with the discovery of 8 cases of infection, consisting of 7 men with a history of same-sex relationships (MSM) and 1 housewife (IRT). This community service aims to increase awareness and understanding of community leaders, representatives of RT, MUI, and posyandu cadres regarding the prevention and control of HIV and AIDS. The methods used include material presentation, participatory discussion, and mentoring with a participatory approach that involves participants actively. The results of the activity showed an increase in participants ' knowledge of HIV and AIDS issues, the formation of collective awareness of the importance of prevention, and the initiative to establish a village health forum. In conclusion, this program has succeeded in strengthening local capacity and encouraging the birth of sustainable community empowerment, so that Sukamulya village has the potential to become a more caring, inclusive, and empowered community in facing the threat of HIV and AIDS.